Accurate weak lensing of standard candles: II. Measuring [sigma]8 with supernovae - Quartin, Miguel; Marra, Valerio; Amendola, Luca (Arxiv, 2014)
Soon the number of type Ia supernova (SN) measurements should exceed 100,000. Understanding the effect of weak lensing by matter structures on the supernova brightness will then be more important than ever. Although SN lensing is usually seen as a source of systematic noise, we will show that it can be in fact turned into signal. More precisely, the non-Gaussianity introduced by lensing in the SN Hubble diagram dispersion depends rather sensitively on the amplitude sigma8 of the matter power spectrum. By exploiting this relation, we are able to predict constraints on sigma8 of 7% (3%) for a catalog of 100,000 (500,000) SNe of average magnitude error 0.12 without having to assume that such intrinsic dispersion is known a priori. The intrinsic dispersion has been assumed to be Gaussian; possible intrinsic non-Gaussianities in the dataset (due to the SN themselves and/or to other transients) could be potentially dealt with by means of additional nuisance parameters describing higher moments of the intrinsic dispersion distribution function. This method is independent of and complementary to the standard methods based on CMB, cosmic shear or cluster abundance observables.